Water end-uses in public buildings located in Florianópolis-SC - Kammers, Pauline Cristiane (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
This paper presents the estimated water end-uses for ten government buildings located in Florianópolis, state of Santa Catarina. First, the specific water consumption for each appliance was estimated by measuring the water flow rate for each appliance and interviewing users about their habits on water use. Based on such data it was possible to estimate the total water consumption for each building; by comparing these with the water consumption measured by the water service board it was possible to determine the water end-uses for each building. In order to make up for discrepancies on the estimated water consumption, a sensitivity analysis was performed on the data obtained from the interviews; leakages were also searched for. In ten buildings that have been studied, toilets and urinals showed the highest end-uses; both toilet and urinal end-uses together ranged from 44.3% to 84.3%, being 72.1% on average. These results indicate that there is a possibility of using rainwater and reusing greywater in buildings, since major water consumers (toilets and urinals) do not need potable water for their operation.